2019
DOI: 10.1017/sjp.2019.29
|View full text |Cite
|
Sign up to set email alerts
|

Self-criticism, Strivings and Aggressive Behavior in Spanish Children: The Two Sides of Self-Oriented Perfectionism

Abstract: This study analyzes the relationship between the two intrapersonal perfectionism dimensions (i.e., Self-Oriented Perfectionism-Critical, SOP-C, and Self-Oriented Perfectionism-Strivings, SOP-S) and the components of aggressive behavior (cognitive, emotional and motor) in a sample of 804 (48.3% females) Spanish students between the ages of 8 and 11 (M = 9.57; DE = 1.12). The Spanish versions of the SOP-C and SOP-S subscales of the Child/Adolescent Perfectionism Scale and the Aggression Questionnaire were used. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
(73 reference statements)
1
2
0
1
Order By: Relevance
“…Due to the absence of previous studies that have analyzed the relationship between PAT and the motor (i.e., physical and verbal aggression) and cognitive (i.e., hostility) components of aggressive behavior, results about these aggressive components will be discussed in light with the conclusions obtained by studies which examined the relationship between perfectionism traits and aggressive behavior. First, regarding the cognitive component of aggressive behavior, our results coincide with previous research which found a positive relationship between perfectionist traits and hostility in young students (García-Fernández et al, 2017; Vicent, Inglés, Gonzálvez, et al, 2019). Secondly, in respect of the association between PAT and physical aggression, it should be noted that perfectionist traits such as perfectionism oriented to others and socially prescribed perfectionism are positively and significantly linked to aggressive patterns such as physical aggression, including anger and hostility, caused by states of frustration (Stoeber et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Due to the absence of previous studies that have analyzed the relationship between PAT and the motor (i.e., physical and verbal aggression) and cognitive (i.e., hostility) components of aggressive behavior, results about these aggressive components will be discussed in light with the conclusions obtained by studies which examined the relationship between perfectionism traits and aggressive behavior. First, regarding the cognitive component of aggressive behavior, our results coincide with previous research which found a positive relationship between perfectionist traits and hostility in young students (García-Fernández et al, 2017; Vicent, Inglés, Gonzálvez, et al, 2019). Secondly, in respect of the association between PAT and physical aggression, it should be noted that perfectionist traits such as perfectionism oriented to others and socially prescribed perfectionism are positively and significantly linked to aggressive patterns such as physical aggression, including anger and hostility, caused by states of frustration (Stoeber et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, studies on perfectionism should be continued, since previous works have warned of its negative influence on affected individuals (Babapour et al, 2015; Flett & Hewitt, 2014). This appears to be caused by its cognitive, emotional, and behavioral foundations (Newman et al, 2019) and due to the association of multiple and diverse psychopathological constructs in both adults (Buzzichelli et al, 2018; Gautreau et al, 2015; Mahmoodi-Shahrebabaki, 2017) and children/youth (Inglés et al, 2016; Vicent, Inglés, & García-Fernández, 2019; Vicent, Inglés, Gonzálvez, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…También en la edad infantil, altos niveles de perfeccionismo se han relacionado con otros problemas de salud mental como es el caso de la conducta agresiva en sus componentes cognitivo -hostilidad-, fisiológico-emocional -ira-y motor (García-Fernández, Vicent, Inglés, Gonzálvez, & Sanmartín, 2017;Hewitt et al, 2002;Vicent, Inglés et al, 2019b;Vicent, Inglés, Sanmartín, Gonzálvez, & García-Fernández, 2018). Además, los niños perfeccionistas pueden estar más expuestos al malestar psicológico debido a la carencia de algunos recursos cognitivos que les servirían para desarrollar un afrontamiento efectivo del estrés (Oros, 2005).…”
Section: Introductionunclassified